Pseudo-Goldstones from Supersymmetric Wilson Lines on 5D Orbifolds - Flacke, T; Hassanain, B; March-Russell, J (2005)
We consider a U(1) gauge theory on the five dimensional orbifold $\mathcal{M}_4× S^1/Z_2$, where $A_5$ has even $Z_2$ parity. This leads to a light pseudoscalar degree of freedom $W(x)$ in the effective 4D theory below the compactification scale arising from a gauge-invariant brane-to-brane Wilson line. As noted by Arkani-Hamed et al in the non-supersymmetric $S^1$ case the 5D bulk gauge-invariance of the underlying theory together with the non-local nature of the Wilson line field leads to the protection of the 4D theory of $W(x)$ from possible large global-symmetry violating quantum gravitational effects. We study the $S^1/Z_2$ theory in detail, in particular developing the supersymmetric generalization of this construction, involving a pseudoscalar Goldstone field (the `axion') and its scalar and fermion superpartners (`saxion' and `axino'). The global nature of $W(x)$ implies the absence of independent Kaluza-Klein excitations of its component fields. The non-derivative interactions of the (supersymmetric) Wilson line in the effective 4D theory arising from U(1) charged 5D fields $Φ$ propagating between the boundary branes are studied. We show that, similar to the non-supersymmetric $S^1$ case, these interactions are suppressed by $\exp(-π R m_{Φ})$ where $π R$ is the size of the extra dimension.